PP-001 Validation of cleaning in a multipurpose facility for non-sterile products. (24th March 2015) - Andersen, L; Rasmussen, L; Thorsen, M
Abstract : Background: Preparation in Hospital Pharmacies aims at meeting special patient needs. In general facilities and equipment are intended for preparation of a variety of products containing a diversity of Active Pharmaceutical Ingredients (API). Cleaning validation has to be performed according to EU GMP, which requires limits for Maximum Acceptable Carryover (MAC) to be established based on toxicological evaluations. Furthermore, effectiveness of the cleaning has to be documented using validated methods of analysis. Purpose: To develop models for establishing limits for MAC in general, and for validating the cleaning of equipment used for the preparation of suppositories in particular. Material and methods: A model for establishing limits for MAC was developed in close cooperation with acknowledged toxicologists with experience from food science. The MAC was calculated based on toxicological evaluations and calculations of the total surface area of equipment. Riboflavin was found to be a suitable marker for API and a method was developed in order to detect any residues with a UV lamp. The method was tested for specificity, stability, reproducibility and accuracy. Limit of detection (LOD) was documented by testing a range of different concentrations of riboflavin for UV activity. For hot spots in the equipment it was furthermore documented, that any residues will be detected during the visual control with the UV lamp. Cleaning validation included preparation of a test batch with riboflavin replacing the worst case API. After production the equipment was cleaned using standard procedures. Subsequently visual control was performed and rinse samples from the equipment were analysed for UV activity. Results: The analytical method was validated and LOD was documented to be 0.05 µg/ml – significantly lower than MAC. Cleaning of equipment used for production of suppositories was successfully validated using the riboflavin UV analytical method. Conclusion: Experience from food science can be used to establish limits for MAC. The riboflavin/UV analytical method is highly suitable for validating the cleaning of equipment used for suppositories. References and/or acknowledgements: No conflict of interest.